PENENTUAN FAKTOR BERPENGARUH PADA EKSTRAKSI RIMPANG JAHE MENGGUNAKAN EXTRAKTOR BERPENGADUK - Anggista, Giovani; Pangestu, Ilyas Teguh; Handayani, Dwi; Yulianto, M. Endy; Astuti, Septi Kusuma (Gema Teknologi, 2019)
Giovani Anggista , Ilyas Teguh Pangestu, Dwi Handayani, M. Endy Yulianto, Septi Kusuma, in this paper explain that the main part of ginger used is rhizome. Processed ginger products that can be developed are ginger oleoresin which contains components of gingerol, shogaol, zingerone, resin and essential oils. Ginger oleoresin content ranges from 3.2 - 9.5%, while the content of gingerol in oleoresin is between 14-25% and shogaol between oleoresin. 2.8-7.0%. Considering the benefits of high-antioxidant ginger which functions as an anti-inflammatory and prevents tumor growth, it is necessary to extract the ginger rhizome. The purpose of this study was to determine the factors that most influence the extraction of gingerol from the ginger rhizome using a stirred extractor and relatively good conditions. Experiments were carried out with various solvents, pH and temperature. Solvents 4 liters and 8 liters, pH 4 and 6 and temperatures 60oC and 100oC. The Gingerol content is measured by a VIS spectrophotometer. The most influential factor in extraction of ginger was determined by experimental design 23. The analysis of the results showed that for extracting 500 grams of powdered ginger using water as a solvent, the most influential factor was pH, in this case, at pH 6 containing 4% ginger.